191k views
4 votes
3(2x+6) = 2(4x-5)

plshelp

2 Answers

1 vote

Answer:

x = 14

Explanation:

Step 1: Simplify both sides of the equation.

Step 2: Subtract 8x from both sides.

Step 3: Subtract 18 from both sides.

Step 4: Divide both sides by -2.

User Honza Hejzl
by
5.8k points
6 votes

Answer:

X = 14

Explanation:

3(2x+6) = 2(4x-5)

you will need to multiply the outside number to the numbers in the parentheses so now it's: ( I reordered the terms to give you a heads up)

6x + 18 = 8x - 10

Reordered:

18 + 6x = -10 + 8x

Now let's solve for X

18 + 6x = -10 + 8x

Now combine like terms

18 + -2x = -10

Now subtract 18 to get -2x alone

18 + -2x = -10

-18 -18

Now it's:

-2x = -28

Now divide by -2 to get x alone

-2x = -28

/-2 /-2

And now it's:

X = 14

I hope this helps :)

User Valentin Richer
by
6.2k points